Carbon stocks in coffee farms and secondary forest systems in the Peruvian Amazon rainforest - Vallejos Torres, Geomar (2023)
Secondary forests and coffee cultivation systems with shade trees might have great potential for carbon sequestration as a means of climate change adaptation and mitigation. This study aimed to measure carbon stocks in coffee plantations under different managements and secondary forest systems in the Peruvian Amazon rainforest (San Martín Region). The carbon stock in secondary forest trees was estimated using allometric equations, while carbon stocks in soil, herbaceous biomass, and leaf litter were determined through sampling and laboratory analysis. The biomass carbon stock in secondary forests was 132.2 t/ha, while in coffee plantations with Inga sp. shade trees it was 118.2 t/ha. Carbon stocks were 76.5 t/ha in coffee with polyculture farming, and the lowest amount of carbon was found in coffee without shade trees (31.1 t/ha). The carbon sequestered by coffee plants in all agroforestry systems examined had an average of 2.65 t/ha, corresponding to 4.63 % of the total carbon sequestered, being the highest stored in the coffee system with Inga sp. shade trees. A higher content of glomalin-related soil proteins (GRSP) was found in coffee without shade trees, with 18.5 mg/g. This is evidence that Inga sp. is the most compatible model of shade system for coffee farms. We recommend the conservation of secondary forests due to the greater biomass and carbon storage, and establishing coffee plantations with Inga sp. shade trees for its integral benefits, such as climate change mitigation.